The Relationship Between Immunization Completeness and Incidents of Acute Respiratory Channel Infection Amongst Children in the Working Area Of Puskesmas Gintu - Andriani, Ria; Basri, Burhanuddin (KnE Life Sciences, 2021)
Acute Respiratory Infection is caused by viruses, bacteria or fungi. If not handled properly, Acute Respiratory Infections can cause death in sufferers. Complete immunization is one of the early efforts to prevent this complaint. The purpose of this research is to determine the relationship between completeness of immunization and the prevalence of Acute Respiratory Infection in children under five in the working area of the Gintu Health Center. The research is descriptive and analytical with a cross sectional approach. Samples were taken using the simple random sampling technique, and there were 58 respondents. The instrument in the study was a questionnaire. The results were analysed using the Chi square formula. The result was P value: 0.000 <0.05, from which it can be concluded that there is a relationship between completeness of immunization and the occurence of Acute Respiratory Infections in children under five. Keywords: Completeness of Immunization, Incidence of Acute Respiratory Infection, Children